2008 IEEE International Conference on Global Software Engineering 2008
DOI: 10.1109/icgse.2008.16
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Effective Bridging in Global Software Engineering

Abstract: Globally distributed software engineering involves one or more of geographic, temporal or cultural distances, which empirical studies find have deleterious effects on the efficiency of the software engineering process. There have been some successful examples where one 'bridge' location has facilitated collaboration and coordination across the other locations. Managers might want to use this bridging as a tactic for future projects, even when future collaborations may be composed of very different participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 60 publications
2
23
0
1
Order By: Relevance
“…al. [34] note that "most of the bridges we have found in our research and in the literature are not ones that were developed intentionally as part of organization strategy, but units that have grown out of organizational need, or of the team positioning themselves in this role.". As an example in a study conducted among several distributed networks of people working on requirements engineering, results showed that on average, about one third of the team members were emergent roles [14].…”
Section: B Cooperationmentioning
confidence: 99%
See 3 more Smart Citations
“…al. [34] note that "most of the bridges we have found in our research and in the literature are not ones that were developed intentionally as part of organization strategy, but units that have grown out of organizational need, or of the team positioning themselves in this role.". As an example in a study conducted among several distributed networks of people working on requirements engineering, results showed that on average, about one third of the team members were emergent roles [14].…”
Section: B Cooperationmentioning
confidence: 99%
“…Finally, the clustering structure is a more common structure that conforms to the known disadvantages and challenges of distributed collaboration. Nevertheless, with the right strategic positioning of the team members and the existence of "bridges" or "stars", these challenges can be surpassed [34].…”
Section: A Coordinationmentioning
confidence: 99%
See 2 more Smart Citations
“…The interdependencies such as each sites goal and objectives that are dependent on the other sites have to be taken into consideration while building bridges [Holmström et.al, 2008]. The bridge teams should match the bridging function and team members must be compatible with the cultures they are interacting [Milewski et al, 2008]. A particular location has to be selected based primarily on the existing or real availability of the experienced staff that can support the staffing requirements [Battin et.al, 2001].…”
Section: Activities Not In the Pmbok ® Guide Performed By Gsd Teamsmentioning
confidence: 99%